Andropay- M-Commerce Application For Procurement Of Products Enabled With Barcode Through Mobiles (International Journal of Engineering and Computer Science, 2017)
Modern hand held devices like smart phones and PDA’s have became increasingly powerful in recent years. The extra features added to these devices made them very popular. In particular most cell phones include cameras, processors equal to PC and internet access. As mobile devices became very popular in our day to day life they tend to replace the PC. They will replace the objects like mp3 players, cameras, planners, chequebooks, etc. In short, we will be using them to accomplish our task. One application that falls into that category is ANDROPAY developed for the Google Play- android phones.